Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Quantum space, ground space traversal, and how to embed multi-prover interactive proofs into unentanglement - Gharibian, Sevag; Rudolph, Dorian (14th Innovations in Theoretical Computer Science (ITCS))
Savitch's theorem states that NPSPACE computations can be simulated in PSPACE. We initiate the study of a quantum analogue of NPSPACE, denoted Streaming-QCMASPACE (SQCMASPACE), where an exponentially long classical proof is streamed to a poly-space quantum verifier. Besides two main results, we also show that a quantum analogue of Savitch's theorem is unlikely to hold, as SQCMASPACE=NEXP. For completeness, we introduce Streaming-QMASPACE (SQMASPACE) with an exponentially long streamed quantum proof, and show SQMASPACE=QMA_EXP (quantum analogue of NEXP). Our first main result shows, in contrast to the classical setting, the solution space of a quantum constraint satisfaction problem (i.e. a local Hamiltonian) is always connected when exponentially long proofs are permitted. For this, we show how to simulate any Lipschitz continuous path on the unit hypersphere via a sequence of local unitary gates, at the expense of blowing up the circuit size. This shows quantum error-correcting codes can be unable to detect one codeword erroneously evolving to another if the evolution happens sufficiently slowly, and answers an open question of [Gharibian, Sikora, ICALP 2015] regarding the Ground State Connectivity problem. Our second main result is that any SQCMASPACE computation can be embedded into "unentanglement", i.e. into a quantum constraint satisfaction problem with unentangled provers. Formally, we show how to embed SQCMASPACE into the Sparse Separable Hamiltonian problem of [Chailloux, Sattath, CCC 2012] (QMA(2)-complete for 1/poly promise gap), at the expense of scaling the promise gap with the streamed proof size. As a corollary, we obtain the first systematic construction for obtaining QMA(2)-type upper bounds on arbitrary multi-prover interactive proof systems, where the QMA(2) promise gap scales exponentially with the number of bits of communication in the interactive proof.

On the structure of regularization paths for piecewise differentiable regularization terms - Gebken, Bennet; Bieker, Katharina; Peitz, Sebastian (Journal of Global Optimization)
Regularization is used in many different areas of optimization when solutions are sought which not only minimize a given function, but also possess a certain degree of regularity. Popular applications are image denoising, sparse regression and machine learning. Since the choice of the regularization parameter is crucial but often difficult, path-following methods are used to approximate the entire regularization path, i.e., the set of all possible solutions for all regularization parameters. Due to their nature, the development of these methods requires structural results about the regularization path. The goal of this article is to derive these results for the case of a smooth objective function which is penalized by a piecewise differentiable regularization term. We do this by treating regularization as a multiobjective optimization problem. Our results suggest that even in this general case, the regularization path is piecewise smooth. Moreover, our theory allows for a classification of the nonsmooth features that occur in between smooth parts. This is demonstrated in two applications, namely support-vector machines and exact penalty methods.

Zur Effektivität des europäischen Kronzeugenprogramms - Der Fall des LKW-Kartells - Tiessen, Michelle

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Digitalität, Mediatisierung und Bildung - Megatrends aus medienpädagogischer Perspektive - Herzig, Bardo (Bildung und Digitalität. Analysen - Diskurse - Perspektiven)

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie)
Keywords: General Medicine

Experimental and simulative determination and correction of the effective gap extension in structured coaxial measuring systems - Josch, Sebastian; Jesinghausen, Steffen; Dechert, Christopher; Schmid, Hans-Joachim (Rheologica Acta)
Abstract The use of structured measuring systems to prevent wall slip is a common approach to obtain absolute rheological values. Typically, only the minimum distance between the measuring surfaces is used for further calculation, implying that no flow occurs between the structural elements. But this assumption is misleading, and a gap correction is necessary. To determine the radius correction $$Δ r$$ Δ r for specific geometries, we conducted investigations on three Newtonian fluids (two silicon oils and one suspension considered to be Newtonian in the relevant shear rate range). The results show that $$Δ r$$ Δ r is not only shear- and material-independent, but geometry-dependent, providing a Newtonian flow behaviour in a similar viscosity range. Therefore, a correction value can be determined with only minute deviations in different Newtonian fluids. As the conducted laboratory measurements are very time-consuming and expensive, a CFD-approach with only very small deviations was additionally developed and compared for validation purposes. Therefore, simulation is an effective and resource-efficient alternative to the presented laboratory measurements to determine $$Δ r$$ Δ r for the correction of structured coaxial geometries even for non-Newtonian fluids in the future.
Keywords: rheology; rheometry; suspension; coaxial; correction

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Price Regulation, Quality Competition and Location Choice with Costly Relocation - Hehenkamp, Burkhard; Kaarbøe, Oddvar M.
We consider a model where for-profit providers compete in quality in a price-regulated market that has been opened to competition, and where the incumbent is located at the center of the market, facing high costs of relocation. The model is relevant in markets such as public health care, education and schooling, or postal services. We find that, when the regulated price is low or intermediate, the entrant strategically locates towards the corner of the market to keep the incumbent at the low monopoly quality level. For a high price, the entrant locates at the corner of the market and both providers implement higher quality compared to a monopoly. In any case, the entrant implements higher quality than the incumbent provider. Social welfare is always higher in a duopoly if the cost of quality is low. For higher cost levels welfare is non-monotonic in the price and it can be optimal to the regulator not to use its entire budget. Therefore, the welfare effect of entry depends on the price and the size of the entry cost, and the regulator should condition the decision to allow entry on an assessment of the entry cost.
Keywords: Quality competition; Price regulation; Location choice; Product differentiation

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Thermal conductivity of solid paraffins and several n-docosane compounds with graphite - Paul, Andreas; Baumhögger, Elmar; Dewerth, Mats-Ole; Hami Dindar, Iman; Sonnenrein, Gerrit; Vrabec, Jadran (Journal of Thermal Analysis and Calorimetry)
The technical importance of paraffins as phase change materials (PCM) in heat storage systems increases. Knowledge on the thermal conductivity of paraffins is necessary for the design and optimization of heat storage systems. However, for most paraffins solely the thermal conductivity of the liquid state has been sufficiently investigated. For the solid state, precise thermal conductivity data are only known for a few paraffins, while only generalized values are available for the remainder, some of which contradict each other. In this study, a measurement setup based on the modified guarded hot plate method is developed. It is used to investigate the thermal conductivity of several paraffines in the solid state, including pure n-docosane and its compounds with different types and concentrations of graphite. For n-docosane in the solid state, the thermal conductivity is determined to be 0.49 W/(m K). A particle size of 200 μm with a spherical shape turns out to be optimal to increase the thermal conductivity. This allows the thermal conductivity of a compound with 10% graphite to increase by a factor of three compared to the pure paraffin. Furthermore, significant differences to thermal conductivity data from the literature are found.
Keywords: Physical and Theoretical Chemistry; Condensed Matter Physics

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering